(3bVGjG GbJUGOjI eYGUQI (B:s (3QDjI ef efXhQ GSdGej (B/s - (3YHO GdSdGe, eUWai eMehOs ((3YeGf(B: s (3GdhQGb ddfTQ hGdJhRjY(B, s, 2011)
(3JVjjb GdaLhI GdZPGFjI aj GdYGde GdESdGej(B- (3JaYjd OhQ GdESJUfGY dOi GdHfhc GdESdGejI(B- (3efXeGJ GdYed GdCgdj hOhQgG aj JNaja ef MOI GdabQ (B- (3GdEfYcGSGJ GdSdHjI ddYhdeI GdEbJUGOjI Ydi GdabQ aj GdYGde GdESdGej hSHd GdehGLgI(B- (3CKQ Gdhba Ydi GdESJbQGQ GdEbJUGOj(B- (3OhQ GdLeYjGJ GdNjQjI aj JCgjd GdeYGbjf dEOeGLge aj GdeLJeY(B- (3Jbhje eSjQI GdHMK GdYdej aj eLGd GdJfejI GdESdGejI(B- (3GdEfMQGaGJ GdTQYjI aj HYV GdHfhc GdGSdGejI(B- (3OhQ JbfjGJ GdEJUGdGJ aj OYe GdJfejI GdELJeGYjI hGdEbJUGOjI aj GdhWf GdYQHj(B- (3GdJcGad GdELJeGYj aj GdESdGes
Keywords: (3GdEbJUGOs; (3GdEbJUGO GdESdGejs; (3GdSjGSI GdEbJUGOjIs; (3Hfhc(B- (3Gdabg GdESdGejs